A General Super Element for a Curved Beam - Saavedra-Flores, E (Elsevier Ltd, 2014)
Corrugated panels have gained considerable popularity in a range of engineering applications, particularly in morphing skin applications. The optimum design of these structures needs simple models of the corrugated panels that may be incorporated into multi-disciplinary system models. Considering the geometric and mechanical properties of the corrugated panel, a generic super element of a corrugated core unit cell with elastomeric coating for morphing structures is investigated in this paper. The super element captures the small deformation of a 2D thin curved beam with variable curvature and is based on an exact analytical equivalent model which avoids any homogenization assumption. The stiffness matrix of a general curved beam element for a corrugated unit cell with elastomeric coating is derived. Different geometries are investigated to verify the accuracy and efficiency of the presented super element. The super element uses the geometric and mechanical properties of the panel as variables that may be applied for further topology optimization studies. The parametric studies of different corrugation shapes demonstrate the suitability of the proposed super element for application in further detailed design investigations. © 2014 Elsevier Ltd. All rights reserved.